David Samuel Margoliouth (1920). Mohammedanism. London, Williams & Norgate, 274 Pages. - Çaksen, Hüseyin (Journal of Al-Tamaddun, 2022)
David Samuel Margoliouth (1858-1940), an English orientalist, was briefly active as a priest in the Church of England. He was Laudian Professor of Arabic at the University of Oxford from 1889 to 1937. “Mohammedanism” is a book written by David Samuel Margoliouth. The book included seven chapters as follows: “The Islamic World,” “Mohammed and The Koran,” “The Islamic State,” “Islamic Theory and Practice,” “Islamic Sects,” “Preachers, Saints, and Orders” and “Islamic Art, Literature, and Science Bibliography.”